Life after God: An Encounter with Postmodernism - Bevir, Mark, (Studies in Moral Philosophy ;, 2022)
In this volume, Mark Bevir argues that postfoundationalism is compatible with humanism and historicism. He shows how postmodernists, especially Derrida and Foucault, drew on structuralism and the avant-garde in ways that led them to downplay human agency and historical context. He then explores how we today might recover and rethink humanism and historicism. And, finally, he discusses the critical and ethical practices that such ideas might inspire.